The Effect of Two Methods of Training in Water (Traband dnd Nasm Training) on Pain and Motor Function in Women with Knee Osteoarthritis - Zohreh Mohammadi Kamalabadi; Allahyar Arabmomeni (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Exercise and physical activity have always been recommended as a core treatment for knee osteoarthritis. However, it is unclear which types of exercises have the most splendid effect on this condition. This study aimed to evaluate the impact of two methods of water exercise (Traband exercise and NASM exercise) on pain and motor function in women with knee osteoarthritis. Methods: In this semi-experimental study, with a design pre and post-test and a control group, 45 women with knee osteoarthritis with an average age = 56.5 years and a BMI = 29.04 kg/m2 were purposefully selected and divided into three groups (n = 15); Water Exercise with Theraband, Water Exercise with the NASM Approach and Control randomly. An exercise protocol with Theraband and NASM approach (approved by the Medical College of Georgia for patients with knee osteoarthritis) was performed for eight weeks, three sessions per week, and each session lasted about 60 minutes in the water. Visual Analog Scale (VAS) and physical performance tests of the Osteoarthritis Research Society International (OARSI) were used to estimate the study variables. MANCOVA and post hoc Bonferroni tests were conducted to analyze the data at a significant level (P ≤ 0.05). Results: The results showed that, similarly, in both experimental groups, the amount of pain and the time of tests TUG, 40MW, and SCT decreased significantly (P≥  0.05). In addition, in both experimental groups, there was a significant increase in the scores of the 30-S-CS and 6MWT tests (P≥  0.05). Conclusions: These results showed the beneficial effects of training in water with the traband and training in water with the NASM approach on pain and motor performance indicators. Therefore, the use of these training methods is recommended as a suitable prevention and treatment method for knee osteoarthritis.